Concept of reconstructive body shaping in obesity. Evidence-based therapy algorithm - Dragu, A.; Horch, Raymund E. (Chirurg, 2014)
Interdisciplinary obesity centers are medically required for the successful treatment of obese patients. Due to the dramatic increase in the number of obese patients needing treatment, it is important to develop interdisciplinary therapy approaches based on clinically and scientifically based knowledge with high levels of evidence. The recent S3 guideline "Surgery of the obese" represents such an evidence-based interdisciplinary approach. In this concept, postbariatric plastic surgery has also been integrated. This article presents an evidence-based therapy algorithm that was developed.
EVALuna2:15557